Positively no Filipinos allowed : building communities and discourse - Tiongson, Antonio T., Jr., 1968-; Gutierrez, Edgardo V. (Edgardo Valencia), 1969-; Gutierrez, Ricardo V. (Ricardo Valencia), 1971- (Asian American history and culture., 2006)
Essays challenging conventional narratives of Filipino American history and culture.